Construção e validação de álbum seriado para promoção da autoeficácia de pais e/ou cuidadores no manejo e controle da asma infantil - Vasconcelos, Flávia Ximenes (2021)
Asthma is a chronic non-communicable inflammatory disease of the lower respiratory tract, which, although treatable, has consequences for children's health. Health education interventions using educational materials that promote the development of self-efficacy by parents and/or caregivers may have an influence on the quality of care offered to asthmatic children and their quality of life. Given the above, the aim was to develop and validate the content and appearance of a flipchart to promote the self efficacy of parents and/or caregivers in the management and control of childhood asthma. This is a methodological study in which the flipchart entitled “Children's asthma: you are able to control!” was consctructed, based on the items of the scale Self-efficacy and level of control of your child's asthma, in the educational booklet “You are able to control your child's asthma - Shall we learn together? ”and on the Albert Bandura's Self-Efficacy Theory. The flipchart consists of 27 pages divided into four parts: I - Cover and introductory information (summary, presentation, how to use the album and good communication techniques); II - Introduction to asthma; III - Information on asthma control and management; IV - Asthma and covid-19. After the construction of the educational material, it was submitted to a content and appearance validation process by 25 content judges (16 professors in the field of nursing and 9 assistant nurses) and three technical judges (area of communication and design). The validation was performed by assessing language clarity, practical pertinence and theorethical relevance, with calculation of Content Validity Coefficient (CVC). As results, the flipchart pages were evaluated as validated if they reached CVC ≥ 0.80 for content judges and CVC ≥ 0.70 for technical judges. The total CVC of the flipchart was 0.96 according to the evaluation of the content judges and 0.83 according to technical judges. The Material Adequacy Assessment (SAM) instrument was used to assess the suitability of the flipchart for use with a target audience. The educational material was rated “superior”, with a total score of 92.67% for content judges and 73.81% for technical judges. Changes were made to the flipchart after the validation process, according to the judges' suggestions and a second version of the material was finalized. It can be concluded that the flipchart constructed is valid and has a high degree of recommendation for use with parents and/or caregivers in the control and management of childhood asthma.